Attributions of responsibility for helping and doing harm evidence for confusion of responsibility - Cacioppo, John T.; Losh, Mary E. (1986)
The social inhibition of helping is well documented, and this phenomenon has been explained in terms of the general processes of audience inhibition, social influence, and diffusion of responsibility. In the present research, we adapted the paradigm used in studies of the attribution of responsibility for an accident to examine a specific audience-inhibition process that may contribute to the social inhibition of helping. Evidence from two experiments showed that an individual who adopted the perspective of a helper following an accident expected to be held increasingly responsible by arriving onlookers for the victim's plight as the number of extant bystanders increased. Results also indicated that there was an objective basis for this expectation: Subjects who adopted the perspective of a newly arriving onlooker increasingly attributed responsibility for doing harm to the individual helping the victim in the accident as the number of bystanders described as already at the scene increased. The distinction between confusion and diffusion of responsibility is emphasized, and limitations to confusion of responsibility for accidents are discussed.
Social inhibition of helping -- Confusion of responsibility -- Discussion.
Photocopy.
Includes bibliographical references (page 105)
Keywords: Social influence; Social role; Social service